Physical Properties of Ti45Zr38Fe17 Alloy and Its Amorphous Hydride - Antoni Żywczak; Łukasz Gondek; Joanna Czub; Piotr Janusz; Nivas Babu Selvaraj; Akito Takasaki (Energies, 2022)
The alloys based on Ti-Zr are considered an excellent candidate for hydrogen storage applications. In this communication, we report the results of Fe substitution for Ni in the well-known Ti45Zr38Ni17 compound. The parent and related compounds can be obtained as amorphous powders, transforming into the quasicrystalline phase (i-phase) after annealing. The amorphous Ti45Zr38Fe17 phase is transformed into the icosahedral quasicrystalline state, and it is a quasi-continuous process. The i-phase is well-developed close to 500 °C. At higher temperatures, the quasicrystal structure transforms into the other phase: the w-phase (an approximant to the crystalline phase) and another crystal phase with a small addition of the FeZr3 and the Fe2(ZrTi)3. The amorphous Ti45Zr38Fe17 phases can be hydrogenated while maintaining the amorphous nature, which constitutes another very fascinating research field for our group. The investigated alloy shows a good capacity for gaseous H2 at level 2.54 wt.% at elevated temperatures. The ferromagnetic signal of the amorphous TiZrFe comes from magnetic nanocrystallites in the amorphous matrix. After heating, the magnetic signal significantly decreases due to the lack of long-range magnetic ordering in the i-phase of the Ti45Zr38Fe17 alloy.